DIGITAL-BASED COLLABORATIVE COMMUNICATION STRATEGY IN MANAGING STAKEHOLDERS - Octory, Gadis; Yananto, Yananto; Sandy, Sandy; Sabena, Sabena (Journal of Digital Media Communication, 2025)
This study explores the dynamics of digital-based collaborative communication strategies in managing student-led events, with UMB Talks 2024 at Universitas Mercu Buana as a case study. First, background. The research is grounded in Habermas’s Theory of Communicative Action and strategic communication, emphasizing mutual understanding and stakeholder engagement in digital environments. It aims to develop a conceptual model of collaborative digital communication in academic settings. A qualitative-descriptive approach was adopted. Data were gathered through in-depth interviews, participatory observation, and document analysis involving student leaders, academic mentors, and external speakers. The study applied stakeholder mapping to identify key actors in the event’s communication process. Findings reveal that tools like WhatsApp and Google Drive enhanced coordination, documentation, and consensus building in a temporary organizational setting. Communication was structured through vertical, horizontal, and diagonal flows, reflecting deliberative practices and ethical engagement. The proposed model includes adaptive channels, flexible structures, and a crisis response system, offering theoretical and practical insights for youth event management. The study shows that digital communication is central to participatory learning and resilient collaboration in higher education. It contributes to communication theory by linking digital affordances with deliberative engagement, and offers a framework applicable to future student-led initiatives.